Естетична цінність ландшафту як передумова створення маршрутів екотуризму - Бучко, Жанна; Гохмут, Зденко (Чернівці: Зелена Буковина, 2007)
Proposals of reservation and rational use of aesthetic potential of landscapes for tourism are offered. The main direction of use of results aesthetic evaluation of landscapes should become creation of ecotourism routes in territories with a high degree of aesthetic value.
BUKOVYNA ETHNOTOURISM: TRENDS AND POSSIBILITIES FOR CROSS-BORDER TOURISM
AESTHETIC VALUE OF LANDSCAPE AS BASIS OF ECOTOURISM ROTES CREATION
Keywords: ЕСТЕТИЧНА ЦІННІСТЬ ЛАНДШАФТУ; ЕКОТУРИЗМ; Туристичний маршрут